Testament from a prison cell - Aquino, Benigno S. (Makati City, Philippines : Benigno S. Aquino Jr. Foundation, 1988)
Ninoy was determined that this book should reach his people and so many children and I smuggled out the manuscript, page by page.
1. Claims and realities -- 2. Three generations -- 3. Philippine communism -- 4. A Christian democratic vision -- 5. Manifesto for a free society -- 6. A totalitarian regime -- 7. Evidence tortured into existence -- 8. RA 1700 -- the anti subversion act
Includes index.
Keywords: AQUINO, BENIGNO S